Synthesis of imine-derived triazines with Donor–Acceptor properties. (1st April 2016) - Corrochano, Diego R.; de la Hoz, Antonio; Sánchez-Migallón, Ana María; Caballero, Rubén; Ramírez, José R.
Abstract: The design of new systems with Donor–Acceptor properties is of great interest for the construction of optoelectronic new devices. Considering the strong supramolecular interaction of triazines with graphene a series of imine-derived triazines with Donor–Acceptor properties have been designed. These compounds have been prepared in good to excellent yields (47–92%) using Green conditions, i.e. microwave irradiation in the absence of an acid catalyst. Their properties as Donor–Acceptor systems have been studied by Ultraviolet–visible and fluorescence spectroscopy and by electrochemical studies. These imine derived triazines are blue-violet emitters (ca. 396 nm) and show large Stokes shifts (c.a. 6700 cm −1 ) and the electrochemical studies shows a high degree of communication between the acceptor triazines and the donor moieties (oxidation potentials up to 1.10 V). These characteristics makes them excellent candidates for the interaction with graphene and the construction of optoelectronic devices, as blue Light Emitting-Diodes (LEDs). Highlights: New Donor–Acceptor systems based on triazine have been designed. A Green synthesis of imine derived triazines has been reported. Communication between the Donor and acceptor moieties was high.